Ray Tracing-Based Modeling of Bifacial Photovoltaic Systems in Greenhouse Agrivoltaics - Endang Widiyawati; Subiyanto Subiyanto; Siti Ridloah; Budi Sunarko; Bagaskoro Saputro; Rizky Ajie Aprilianto; Mario Norman Syah; Abdurrakhaman Hamid Al-Azhari; Deyndrawan Sutrisno; Aisya Fathimah; Apriansyah Wibowo; I Gede Bagus Jayendra (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
This work presents an enhanced ray tracing-based modeling framework to optimize bifacial photovoltaic energy generation and crop productivity within greenhouse environments. The proposed framework integrates a ray tracing-based optical and electrical model to simulate light dynamics and energy generation within greenhouse structures. The optical model incorporates Uniform Distribution of rear-irradiance (UF) and Non-Uniform Distribution of rear-irradiance (NUF) principles to simulate irradiance distribution, shading, and reflection, using Light Saturation Point (LSP) and Photosynthetically Active Radiation (PAR) measurements. The electrical model estimates energy yield using the LambertW function based on incident and transmitted light through photovoltaic arrays. Five types of greenhouse structures using plastic and SG80 materials are analyzed to assess their impact on system performance under various conditions. The evaluation showed that integrating bPV increased rear-side energy captured by 25-30%. The optimal configuration was achieved by combining a plastic cover with a checkerboard pattern, resulting in up to 5% higher performance than the 35° tilt setup and offering enhanced light distribution uniformity. Although the average soil irradiance of 170.801 W/m² slightly exceeded the light saturation threshold of 164.7 W/m², it remained within a safe range that supports efficient photosynthesis without causing photoinhibition.